ANALISIS KEMAMPUAN KIAMBANG (Salvinia molesta) UNTUK MENURUNKAN KONSENTRASI ION LOGAM Cu (II) PADA MEDIA TUMBUH AIR - Dewi Eka Yuliani; Saibun Sitorus; Teguh Wirawan (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2013)
This research was purposed to know about the water lettuce (Salvinia molesta) absorption ability for metal Cu (II) ion and the influence of plant sum variation and its contact time. The simulation is done by planting the water lettuce (Salvinia molesta) at water media as a growing place which prepared in 5 place that each be volumed by 5 l the plant of Cu solution as 20 mg/L, Then, the water lettuce (Salvinia molesta) also be volumed as 0 (blank), 10, 15, 20 and 25 as its variation. Then, this research also variated its contact time as 0, 3, 6, 9, 12, 15, 18 and 21 days. The concentration of metal Cu (II) ion in plant media was analyzed with Atomic Absorption Spectrophotometer (AAS). The research showed that the water lettuce (Salvinia molesta) was capable to absorp the metal Cu (II) ion with the optimal absorbtion happened at the 9th day in 15 plants sum of variation, with total percentage of the metal Cu (II) is absorbted to 81.68 %.Keyword: Water lettuce (Salvinia molesta), Cu (II), metal, water